An Analysis of Declarative and Interrogative Sentences In “Don’t Look Up” Movie - Agustinus Fransiskus; Widi Syahtia Pane; Godefridus Bali Geroda (Inquest Journal, 2023)
AbstractBackground:Human communicate by using sentences in daily life. There are two types pf sentences usually used by people in an utterance declarative and interrogative sentence and it is important to know the meaning for every structure of sentences in order to avoid misunderstand between people. This study aims to analyze types and deep structure of Declarative and Interrogative sentences that appeared in “Don’t Look Up” MovieMethodology: The researcher used a design for content analysis. The characters shown in the film "Don't Look Up" are the focus of this investigation. The study's focus was on the declarative and interrogative language employed by the movie's characters. A checklist served as the study's main tool.Findings: The researcher discovered there are 117 declarative sentences, 79 (67.6%) positive declarative sentences, and 38 (31.5%) negative declarative sentences. Meanwhile, for the interrogative sentences, the researcher found there are 132 interrogative sentences, 77 (58.3%) wh questions, 54 (40.9%) yes-no questions, and 1 (0.7%) alternative question and the deep structure of declarative sentence used Subject and Noun phrase to create sentence and for the interrogative sentence used Complementizer and Sentence for its structure.Conclusion: In declarative types, the frequent used types declarative sentence was positive declarative sentence and for interrogative sentences, the character most used was wh questions in dialogue. (Brown & Miller, 1991) as a guidance theory to draw the tree diagram where the deep structure of a declarative sentence consists of a noun phrase and verb phrase while the interrogative sentence needs to attach the wh-question word or the auxiliary to the complementizer and followed by a noun phrase and verb phraseOriginality: This research can used for references and help student or readers to understand deeper the interrogative and declarative sentence and its structure.